Design of River Galeh Bridge Temanggung Regency with Reinforced Concrete T-Beam Structure - Asri Nurdiana; Shifa Fauziyah; Moh Nur Sholeh (Jurnal Proyek Teknik Sipil, 2021)
The old bridge of Sungai Galeh is a short span bridge with a reinforced concrete beam superstructure and a masonry bottom structure. This bridge is planned to be replaced for renovation. The replacement Sungai Galeh bridge is planned with the upper structure using reinforced concrete T-beams and the lower structure using reinforced concrete cantilever abutments. The purpose of this paper is to re-plan the Sungai Galeh Bridge in order to provide services for traffic users safely and comfortably. From the analysis results, the dimensions of the reinforced concrete T-beam are 40 x 80 and the dimensions of the diaphragm are 25 x 45.